Theory of high temperature superconductivity : a conventional approach - 508703 Mishonov, Todor M.; Penev, Evgeni S. (Singapore ; Hackensack, N.J. : World Scientific Publishing, 2011)
Includes bibliographical references (p. 225-255) and index